A Ni x Co 1-x / MoP@NC nanocatalyst and its preparation method and application

By embedded with MOP nanoparticles on nitrogen-doped hollow carbon balls and formed NIXCO1-X/MOP@NC nano-heterogeneous structure, the problem of low non-precious metal catalyst activity and reunion are easy to reunite. The effect of hydrogen.

CN118384910BActive Publication Date: 2025-01-24JIANGXI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410830916.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-26
Publication Date
2025-01-24
Estimated Expiration
2044-06-26

AI Technical Summary

Technical Problem

In the prior art, non-precious metal catalysts have low catalytic activity during the hydrogen production process of ammonia borane hydrolysis, are prone to agglomeration, have few active sites, and are difficult to meet actual production needs.

Method used

Using NIXCO1-X/MOP@NC nano-catalysts, MOP nanoparticles are embedded in nitrogen-doping hollow carbon balls, and nixm is forming nano-heterogeneous structures with NIXCO1-X nanoparticles to enhance the electronic density of electronic transfer capabilities and active sites. Essence

Benefits of technology

The catalytic activity is significantly improved, achieving 100% H2 selectivity and good durability. The TOF value reaches 257 min-1, which is suitable for efficient catalysis of hydrogen production from the hydrolysis of ammonia borane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118384910B_ABST
    Figure CN118384910B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of catalysts and specifically discloses a Ni x Co 1‑x / MoP@NC nanocatalyst and its preparation method and application. x Co 1‑x The nanoparticles and the MoP nanoparticles form a nano heterostructure, wherein 0<x≤1; the content of Ni in the nanocatalyst is 0.1-18.2 wt%, the content of Co is 0-4.5 wt%, and the average particle size is 4.7-6.9 nm. Preparation method: MoP@NC powder is dispersed in deionized water, a nickel source precursor and a cobalt source precursor are added or only a nickel source precursor is added, ultrasound is applied, and a reducing agent is added to obtain the catalyst. The catalyst can be used to catalyze the hydrolysis of ammonia borane to produce hydrogen. The Ni synthesized by the present invention x Co 1‑x / MoP@NC catalyst exhibits extremely high catalytic performance, 100% H2 selectivity and good durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and more specifically relates to a Ni x Co 1-x / MoP@NC nanocatalyst and its preparation method and application. Background Art

[0002] As one of the most promising alternatives to fossil fuels, hydrogen has attracted increasing attention due to its high energy density, zero carbon emissions and renewable properties. However, efficient and safe hydrogen storage remains one of the challenging obstacles to a hydrogen-based economy and society. Finding appropriate strategies to solve the difficulties in hydrogen storage and transportation is necessary and critical. Chemical hydrogen storage materials have attracted widespread attention due to their high hydrogen content and mild dehydrogenation temperature. Among potential hydrogen storage materials, ammonia borane (NH3BH3, AB) has become a promising candidate material due to its ultra-high hydrogen content (19.6wt%), high volumetric hydrogen storage density (0.145 kgH2 / L) and good chemical stability. In the presence of an appropriate catalyst, 1 mole of NH3BH3 can be hydrolyzed to produce 3 moles of H2 at room temperature, as shown in reaction equation (1).

[0003] NH3BH3+2H2O→NH4BO2+3H2 (1)

[0004] However, most of the current efficient catalysts for AB hydrolysis to produce hydrogen contain precious metals, and non-precious metal, especially nickel-based alloy catalysts, have been shown to have good activity in the hydrolysis of AB, but their catalytic activity is still unsatisfactory compared with precious metal-based catalysts. Therefore, there is an urgent need to develop cost-effective non-precious metal catalysts for the rapid catalytic hydrolysis of AB.

[0005] The prior art reports that precious metal catalysts catalyze the hydrolysis of ammonia borane to produce hydrogen and show good catalytic performance. However, from the perspective of practical application, it is very important to develop efficient, low-cost and stable non-precious metal catalysts and further improve their activity under suitable conditions. Subsequently, the use of different carriers (γ-Al2O3, SiO2 and C) to load non-precious metals (Co, Ni, Fe, Cu) was studied and it was found that the supported Co and Ni catalysts have good catalytic activity for the production of hydrogen from ammonia borane. Since then, a series of supported non-precious metal catalysts have been used for the hydrolysis of ammonia borane to produce hydrogen, but they often have low hydrogen production activity and cannot effectively activate the reactants AB and H2O in the hydrolysis of ammonia borane. A large number of studies have shown that NiCoNPs are effective catalysts for the hydrolysis of ammonia borane to produce hydrogen. Combining NiCo NPs with substances that activate water and loading them on suitable carriers can effectively increase the electron density of active sites, improve the dispersibility of nanoparticles and reduce the particle size, forming dual active sites with strong interactions, thereby preparing catalysts with excellent performance.

[0006] Molybdenum phosphide (MoP) has been shown to effectively adsorb H2O molecules and accelerate the cleavage of OH bonds. It is a promising material for catalyzing H2O-related reactions such as hydrolysis and water splitting. Its excellent platinum-like electronic structure, high conductivity and good stability have attracted the attention of many researchers. Summary of the invention

[0007] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art, and to provide a Ni x Co 1-x / MoP@NC nanocatalyst is designed to improve the problems of low catalytic activity, easy agglomeration and few active sites of the catalyst to meet the needs of actual production use.

[0008] The technical solution of the present invention is as follows:

[0009] In a first aspect, the present invention provides a Ni x Co 1-x / MoP@NC nanocatalyst, the raw materials for preparation include Ni x Co 1-x Nanoparticles, MoP nanoparticles and nitrogen-doped hollow carbon spheres, the Ni x Co 1-x The nanoparticles form a nanoheterostructure with MoP nanoparticles, and its chemical formula is Ni x Co 1-x / MoP@NC, where 0<x≤1.

[0010] Preferably, the content of Ni in the nanocatalyst is 0.1-18.2 wt%, and the content of Co is 0-4.5 wt%.

[0011] Preferably, the average particle size of the nanocatalyst is 4.7-6.9 nm;

[0012] Preferably, the Ni x Co 1-x The molar ratio of Ni to Co in the nanoparticles is 0.1~10:10~0;

[0013] Preferably, the content of MoP in the nanocatalyst is 7.7-10.9 wt %;

[0014] Preferably, the thickness of the nitrogen-doped hollow carbon sphere is 30-50 nm, and the nitrogen content in the nitrogen-doped hollow carbon sphere is 2.6-3.4 wt %.

[0015] A second aspect of the present invention provides a Ni x Co 1-xPreparation method of / MoP@NC nanocatalyst.

[0016] In order to achieve the above object, the present invention adopts the following technical solution:

[0017] A Ni x Co 1-x The preparation method of the MoP@NC nanocatalyst comprises the following steps:

[0018] MoP@NC powder was dispersed in deionized water, and nickel source precursor and cobalt source precursor or only nickel source precursor were added, and ultrasonic was performed to obtain a uniform mixed solution, and finally a reducing agent was added to obtain Ni x Co 1-x / MoP@NC nanocatalyst.

[0019] Preferably, the nickel source precursor is at least one of nickel chloride, nickel nitrate or nickel sulfate; the cobalt source precursor is at least one of cobalt chloride, cobalt nitrate or cobalt sulfate; and the reducing agent is sodium borohydride.

[0020] Preferably, the mass ratio of the nickel source precursor, the cobalt source precursor, MoP@NC and the reducing agent is 0.1~18.2:0~4.5:10~30:20~30.

[0021] Preferably, the preparation method of MoP@NC comprises the following steps: adding tetrakis(hydroxymethyl)phosphonium chloride to deionized water, and adding aniline dropwise under stirring; subsequently adding ammonium molybdate tetrahydrate and stirring for a certain period of time, washing the product after stirring, and drying to obtain a precursor powder; and finally calcining in a protective atmosphere to obtain MoP@NC black powder.

[0022] Preferably, the preparation method of MoP@NC comprises the following specific steps: adding 450-550 μL of tetrakis(hydroxymethyl)phosphonium chloride to 20-40 mL of deionized water, slowly dropping 200-300 μL of aniline under vigorous stirring to successfully polymerize it; then adding 0.3-0.4 g of ammonium molybdate tetrahydrate and stirring for 8-16 hours, washing the product after stirring with deionized water and anhydrous ethanol, drying in an oven at 70-90°C to obtain a precursor powder, and finally evaporating the mixture at 0.5-1.5°C·min in a protective atmosphere. -1 The heating rate was increased to 800~900℃ and maintained for 0.5~1.5 h to obtain MoP@NC black powder.

[0023] A third aspect of the present invention provides a Ni x Co 1-x Application of / MoP@NC nanocatalyst in catalytic hydrolysis of ammonia borane to produce hydrogen.

[0024] Preferably, the temperature for catalyzing the hydrolysis of ammonia borane to produce hydrogen is 288-303 K.

[0025] The present invention has at least one of the following beneficial effects:

[0026] The present invention uses aniline and tetrakis hydroxymethyl phosphonium chloride to organically polymerize in deionized water at room temperature, introduces ammonium molybdate tetrahydrate and stirs, and finally calcines at high temperature in a protective atmosphere to prepare MoP@NC with a porous hollow carbon sphere structure. It is used as a carrier precursor to prepare Ni supported on MoP@NC by a simple in-situ reduction method. x Co 1-x Alloy nanoparticle dual active site catalyst (Ni x Co 1-x / MoP@NC). Ni with a particle size of about 4.7~6.9 nm x Co 1-x / MoP heterostructure nanoparticles are highly dispersed on nitrogen-doped hollow carbon spheres. Combining Ni-based alloys with MoP to construct dual active centers with heterostructures can enhance the electron transfer ability and increase the electron density of active sites. It can also successfully activate AB molecules (ammonia borane, molecular formula NH3BH3) while effectively adsorbing and activating H2O molecules. Through TEM, EDX, XRD, UV-Vis, water contact angle tests and XPS characterization analysis, it can be seen that the introduction of MoP NPs can make nitrogen-doped hollow carbon spheres highly hydrophilic, can effectively adsorb H2O molecules and accelerate the cleavage of OH bonds, and enhance its adsorption capacity for metal precursor salt ions, regulate the electronic structure of the metal, and finally prepare a nano-heterostructure catalyst with small and uniform particle size and stronger electronic effect.

[0027] The Ni synthesized by the present invention x Co 1-x / MoP@NC catalyst showed extremely high catalytic performance, 100% H2 selectivity and good durability. x Co 1-x The TOF value of / MoP@NC for the hydrolysis of ammonia borane at 298 K is 257 min -1 The development of the efficient and stable catalyst provided by the present invention accelerates the practical application of ammonia borane as an efficient hydrogen supplier in fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0029] Figure 1 The Ni obtained in Example 1 of the present invention x Co 1-x Transmission electron microscopy images of / MoP@NC nanocatalysts (shown in a), Ni x Co 1-x / MoP heterojunction nanoparticle size distribution diagram (shown in b), selected area electron diffraction diagram (shown in c) and high-resolution transmission electron microscopy diagram (shown in d);

[0030] Figure 2 The Ni obtained in Example 1 of the present invention x Co 1-x EDX spectrum of / MoP@NC nanocatalyst;

[0031] Figure 3 1 is a contact angle test diagram of MoP@NC, MoP and NC obtained in Example 1 of the present invention;

[0032] Figure 4 In Example 1 of the present invention, Ni 2+ Co 2+ Mix with MoP@NC and let the supernatant stand. 2+ Co 2+ Mix the supernatant and Ni with NC and let it stand 2+ Co 2+ UV-visible absorption spectrum of the mixed static supernatant;

[0033] Figure 5 The Ni obtained in Example 1 of the present invention x Co 1-x / MoP@NC nanocatalyst and Ni x Co 1-x / X-ray diffraction patterns of NC and NC;

[0034] Figure 6 The Ni obtained in Example 1 of the present invention x Co 1-x / MoP@NC nanocatalyst and Ni x Co 1-x / NC X-ray photoelectron spectrum, with the abscissa representing the binding energy of 850-885 eV;

[0035] Figure 7 The Ni obtained in Example 1 of the present invention x Co 1-x / MoP@NC nanocatalyst and Ni x Co 1-xX-ray photoelectron spectrum of / NC, with the abscissa representing the binding energy of 775-805 eV;

[0036] Figure 8 The Ni obtained in Examples 1 to 5 of the present invention and Comparative Example 1 x Co 1-x Performance test diagram of / MoP@NC composite catalyst catalyzing the hydrolysis of ammonia borane to produce hydrogen at 298K;

[0037] Fig. 9 The Ni obtained in Examples 1 and 6 to 8 of the present invention x Co 1-x / MoP@NC nanocatalyst catalyzes the hydrolysis of ammonia borane to produce hydrogen at 298K.

[0038] Fig.10 The Ni obtained in Example 1 of the present invention x Co 1-x / MoP@NC nanocatalyst catalyzing the hydrolysis of ammonia borane to produce hydrogen performance test diagram at different temperatures.

[0039] Fig.11 The Ni obtained in Example 1 of the present invention x Co 1-x / MoP@NC nanocatalyst catalyzes the hydrolysis of ammonia borane to produce hydrogen at 298 K for cyclic use performance test.

[0040] Among them, the Ni prepared in Example 1 x Co 1-x / MoP@NC nanocatalyst is specifically Ni 0.8 Co 0.2 / MoP@NC nanocatalyst, Figure 1 , Figure 4-Figure 7 In order to simplify the writing, "Ni 0.8 Co 0.2 " is simplified to "NiCo" and "Ni 2+ Co 2+ ",Right now Figure 1 , Figure 4-Figure 7 "NiCo" and "Ni 2+ Co 2+ "Actually refers to "Ni 0.8 Co 0.2 ”. DETAILED DESCRIPTION

[0041] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0042] One embodiment of the present invention provides a Ni x Co 1-x / MoP@NC nanocatalyst, the nanocatalyst is composed of Ni x Co 1-x The nanoparticles are uniformly dispersed on the nitrogen-doped hollow carbon spheres modified with MoP nanoparticles on the surface. x Co 1-x The nanoparticles form a nano heterostructure with MoP nanoparticles, and the chemical formula of the nano catalyst is Ni x Co 1-x / MoP@NC, where 0<x≤1.

[0043] Due to the strong adsorption of metal salt ions by MoP, Ni x Co 1-x The nanoparticles are uniformly dispersed around the MoP NPs in the N-doped hollow carbon spheres, forming a Ni x Co 1-x / MoP nanoheterostructure. x Co 1-x / MoP ultrafine heterostructure NPs usually have high surface energy, which makes them easy to aggregate into larger particles, resulting in reduced catalytic activity. The present invention embeds MoP NPs in N-doped carbon (NC) materials with special morphology, which not only disperses and protects the active nanoparticles from aggregation and erosion, but also stabilizes the ultrafine heterostructure NPs on N-doped hollow carbon spheres to further increase the catalytic performance.

[0044] In a specific embodiment of the present invention, the content of Ni in the nanocatalyst is 0.1-18.2 wt %, preferably 3-14 wt %, more preferably 5-13%, further 7-12%, and further 9-10.5%.

[0045] In a specific embodiment of the present invention, the content of Co in the nanocatalyst is 0-4.5 wt %, preferably 0.5-4 wt %, more preferably 1-3.5%, further 1.5-3%, and further 2-3%.

[0046] In a specific embodiment of the present invention, the Ni x Co 1-x The molar ratio of Ni to Co in the nanoparticles is 4-10:0-8; preferably 5-9:2-6, and more preferably 7-9:1-3.

[0047] In a specific embodiment of the present invention, the average particle size of the nanoparticles in the nanocatalyst is 4.7-6.9 nm, and the nanoparticles in the nanocatalyst are uniformly dispersed.

[0048] In a specific embodiment of the present invention, the content of MoP nanoparticles in the nanocatalyst is 7.7-10.9 wt%.

[0049] In a specific embodiment of the present invention, the thickness of the nitrogen-doped hollow carbon sphere is 30-50 nm, and the nitrogen content in the nitrogen-doped hollow carbon sphere is 2.6-3.4 wt %.

[0050] Another embodiment of the present invention provides a Ni x Co 1-x The preparation method of the MoP@NC nanocatalyst comprises the following steps:

[0051] MoP@NC powder is dispersed in deionized water, and nickel source precursor and cobalt source precursor are added, or only nickel source precursor is added, and ultrasonication is performed to obtain a uniform mixed solution, and finally a reducing agent is added to obtain Ni x Co 1-x / MoP@NC nanocatalyst.

[0052] In a specific embodiment of the present invention, the nickel source precursor is at least one of nickel chloride, nickel nitrate or nickel sulfate; the cobalt source precursor is at least one of cobalt chloride, cobalt nitrate or cobalt sulfate; and the reducing agent is sodium borohydride.

[0053] In a specific embodiment of the present invention, the mass ratio of the nickel source precursor, the cobalt source precursor, MoP@NC and the reducing agent is 0.1-18.2: 0-4.5: 10-30: 20-30. Preferably, it is 3-14: 0.5-4: 12-28: 21-29, more preferably 5-13: 1-3.5: 14-26: 22-28, further, it can be 7-12: 1.5-3: 16-24: 23-27, and further, it can be 9-10.5: 2-3: 18-22: 24-26.

[0054] In a specific embodiment of the present invention, the preparation of MoP@NC includes the following steps: adding tetrakis hydroxymethylphosphonium chloride to deionized water, and adding aniline dropwise under stirring; then adding ammonium molybdate tetrahydrate and stirring for a certain period of time, washing the product after stirring, and drying to obtain a precursor powder; and finally calcining in a protective atmosphere to obtain MoP@NC black powder.

[0055] In a specific embodiment of the present invention, the preparation of MoP@NC includes the following specific steps: adding 450-550 μL of tetrakis(hydroxymethyl)phosphonium chloride to 20-40 mL of deionized water, slowly dropping 200-300 μL of aniline under vigorous stirring to successfully polymerize it; then adding 0.3-0.4 g of ammonium molybdate tetrahydrate and stirring for 8-16 hours, washing the product after stirring with deionized water and anhydrous ethanol, drying in an oven at 70-90°C to obtain a precursor powder, and finally evaporating in a protective atmosphere at 0.5-1.5°C·min -1 The heating rate was increased to 800~900℃ and maintained for 0.5~1.5h to obtain MoP@NC black powder.

[0056] Preferably, the preparation of MoP@NC comprises the following steps: 500 μL of tetrakis(hydroxymethyl)phosphonium chloride is added to 30 mL of deionized water, and 250 μL of aniline is slowly added dropwise under vigorous stirring to successfully polymerize the mixture. Subsequently, 0.35 g of ammonium molybdate tetrahydrate is added and stirred at room temperature for 12 hours. After stirring, the product is washed by centrifugation with deionized water and anhydrous ethanol for multiple times, and dried in an oven at 80°C to obtain a precursor powder (THPC-AN-Mo). Finally, the product is heated in an Ar atmosphere at 1°C·min -1 The temperature was raised to 850 °C and maintained for 1 h to obtain MoP@NC black powder.

[0057] Another embodiment of the present invention provides the Ni x Co 1-x / MoP@NC nanocatalyst or the Ni x Co 1-x Application of / MoP@NC nanocatalyst in catalytic hydrolysis of ammonia borane to produce hydrogen.

[0058] In a specific embodiment of the present invention, the temperature at which the nanocatalyst catalyzes the hydrolysis of ammonia borane to produce hydrogen is 288-303 K.

[0059] Ni x Co 1-x NPs are uniformly dispersed around MoP NPs on the surface of nitrogen-doped porous hollow carbon spheres (NCs). The modification of MoPNPs can not only improve the hydrophilicity of porous NCs, effectively activate H2O molecules and accelerate the cleavage of OH bonds, but also adsorb Ni x Co 1-x NPs construct Ni with strong coupling x Co 1-x / MoP heterogeneous structure, providing high-performance dual active centers. Therefore, the catalyst prepared by the present invention has the characteristics of small and uniform particle size, excellent electron transport structure, and multiple catalytic active sites, and can efficiently catalyze the hydrolysis of ammonia borane to produce hydrogen with a selectivity of 100% and a conversion frequency (TOF) of up to 257 min at 298 K. -1 , and has good cycle stability, and is a catalyst with development prospects.

[0060] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.

[0061] Example 1

[0062] 1) Preparation of MoP@NC: 500 μL of tetrakis(hydroxymethyl)phosphonium chloride was added to 30 mL of deionized water, and 250 μL of aniline was slowly added under vigorous stirring to achieve successful polymerization. Subsequently, 0.35 g of ammonium molybdate tetrahydrate was added and stirred at room temperature for 12 hours. After stirring, the product was washed with deionized water and anhydrous ethanol by centrifugation several times, and dried in an oven at 80°C to obtain a precursor powder (THPC-AN-Mo). Finally, the product was heated in an Ar atmosphere at 1°C min -1 The temperature was raised to 850 °C and maintained for 1 h to obtain a black powder.

[0063] 2) Ni x Co 1-x Preparation of / MoP@NC composite nanocatalyst: 20 mg of the black powder obtained in step 1) was dispersed in 5 mL of deionized water and ultrasonicated for 10 min. 0.04 mmol of nickel chloride and 0.01 mmol of cobalt chloride were added and ultrasonicated at room temperature for 20 min to obtain a uniform mixed solution. Finally, 25 mg of sodium borohydride was added for reduction until no bubbles were generated. The metal molar ratio of Ni and Co was 8:2, and the Ni and Co loadings were 10.2 wt% and 2.6 wt%, respectively. 0.8 Co 0.2 / MoP@NC nanocatalyst.

[0064] Example 2

[0065] The metal molar ratio of Ni and Co in step 2) of Example 1 was adjusted to 10:0, and the other steps were the same as Example 1 to obtain a Ni / MoP@NC nanocatalyst.

[0066] Example 3

[0067] The metal molar ratio of Ni and Co in step 2) of Example 1 was adjusted to 9:1, and the other steps were the same as in Example 1 to obtain Ni 0.9 Co 0.1 / MoP@NC nanocatalyst.

[0068] Example 4

[0069] The metal molar ratio of Ni and Co in step 2) of Example 1 was adjusted to 6:4, and the other steps were the same as in Example 1 to obtain Ni 0.6 Co 0.4 / MoP@NC nanocatalyst.

[0070] Example 5

[0071] The metal molar ratio of Ni and Co in step 2) of Example 1 was adjusted to 4:6, and the other steps were the same as in Example 1 to obtain Ni 0.4 Co 0.6 / MoP@NC nanocatalyst.

[0072] Comparative Example 1

[0073] The metal molar ratio of Ni and Co in step 2) of Example 1 was adjusted to 0:10, and the other steps were the same as in Example 1 to obtain a Co / MoP@NC nanocatalyst.

[0074] Figure 1 The Ni obtained in Example 1 x Co 1-x Transmission electron microscopy images of / MoP@NC nanocatalysts (shown in a), Ni x Co 1-x / MoP heterojunction nanoparticle size distribution diagram (shown in b), selected area electron diffraction diagram (shown in c) and high-resolution transmission electron microscopy diagram (shown in d); Figure 2 The Ni obtained in Example 1 x Co 1-x / MoP@NC nanocatalyst EDX spectrum.

[0075] from Figure 1 It can be seen that the catalyst sample has an obvious hollow carbon sphere structure. x Co 1-x It forms a nano-heterostructure with MoP, and the nanoparticles of the catalyst are evenly dispersed.

[0076] from Figure 2 It can be seen that the catalyst contains Ni, Co, Mo, P, N, and C elements.

[0077] Figure 3 1 is a contact angle test diagram of MoP@NC, MoP and NC obtained in Example 1 of the present invention;

[0078] from Figure 3It can be seen that the MoP@NC obtained after the hydrophobic NC is modified by MoP NPs has a higher hydrophilicity, indicating that MoP water molecules have unique activation ability.

[0079] Figure 4 In Example 1 of the present invention, Ni 2+ Co 2+ Mix with MoP@NC and let the supernatant stand. 2+ Co 2+ Mix the supernatant and Ni with NC and let it stand 2+ Co 2+ UV-visible absorption spectrum of the mixed static supernatant;

[0080] from Figure 4 It can be seen that the Ni x Co 1-x / MoP@NC compared to Ni x Co 1-x / NC has a strong ability to adsorb metal ions, indicating that MoP NPs can easily absorb Ni x Co 1-x NPs are adsorbed around to form a heterogeneous structure.

[0081] Figure 5 The Ni obtained in Example 1 of the present invention x Co 1-x / MoP@NC nanocatalyst and Ni x Co 1-x / X-ray diffraction patterns of NC and NC;

[0082] from Figure 5 It can be seen that NC loads Ni x Co 1-x After metal, Ni appeared x Co 1-x The diffraction peak of MoP (2θ=44.4°) appears after the introduction of MoP NPs. x Co 1-x The diffraction peaks are covered.

[0083] Figure 6 The Ni obtained in Example 1 of the present invention x Co 1-x / MoP@NC nanocatalyst and Ni x Co 1-x / NC X-ray photoelectron spectrum, with the abscissa representing the binding energy of 850-885 eV;

[0084] Figure 7 The Ni obtained in Example 1 of the present invention xCo 1-x / MoP@NC nanocatalyst and Ni x Co 1-x X-ray photoelectron spectrum of / NC, with the abscissa representing the binding energy of 775-805 eV;

[0085] from Figure 6 and Figure 7 All Ni can be found in x Co 1-x There is a strong interaction with MoP, indicating that the formation of a heterointerface is beneficial to the rapid transfer of electrons.

[0086] Example 6

[0087] The amount of MoP@NC in step 2) of Example 1 was adjusted to 10 mg, and the other steps were the same as Example 1 to obtain Ni with Ni and Co loadings of 18.2 wt% and 4.5 wt%, respectively. 0.8 Co 0.2 / MoP@NC nanocatalyst.

[0088] Example 7

[0089] The amount of MoP@NC in step 2) of Example 1 was adjusted to 15 mg, and the other steps were the same as Example 1 to obtain Ni with Ni and Co loadings of 13.1 wt% and 3.3 wt%, respectively. 0.8 Co 0.2 / MoP@NC nanocatalyst.

[0090] Example 8

[0091] The amount of MoP@NC in step 2) of Example 1 was adjusted to 30 mg, and the other steps were the same as Example 1 to obtain Ni with Ni and Co loadings of 7.1 wt% and 1.8 wt%, respectively. 0.8 Co 0.2 / MoP@NC nanocatalyst.

[0092] Example 9

[0093] The nickel salt precursor nickel chloride in step 2) of Example 1 was changed to nickel nitrate, and the other steps were the same as in Example 1 to obtain Ni 0.8 Co 0.2 / MoP@NC nanocatalyst.

[0094] Example 10

[0095] The nickel salt precursor nickel chloride in step 2) of Example 1 was changed to nickel sulfate, and the other steps were the same as in Example 1 to obtain Ni 0.8 Co 0.2 / MoP@NC nanocatalyst.

[0096] Embodiment 11

[0097] The precursor cobalt chloride in step 2) of Example 1 was changed to cobalt nitrate, and the other steps were the same as in Example 1 to obtain Ni 0.8 Co 0.2 / MoP@NC nanocatalyst.

[0098] Example 12

[0099] The precursor cobalt chloride in step 2) of Example 1 was changed to cobalt sulfate, and the other steps were the same as in Example 1 to obtain Ni 0.8 Co 0.2 / MoP@NC nanocatalyst.

[0100] Embodiment 13

[0101] The Ni prepared by Examples 1, 2, 3, 4, 5 and Comparative Example 1 of the present invention x Co 1-x The / MoP@NC nanocatalyst catalyzes the hydrolysis of ammonia borane to produce hydrogen. The catalyst was placed in a 50 mL round-bottom flask containing 5 mL of deionized water, and 31.8 mg (1.0 mmol) of ammonia borane was added at 298 K and atmospheric pressure for reaction. The hydrogen production performance was as follows: Figure 8 The conditions for preparing the catalysts in Examples 1 to 5 and the results of the catalytic reactions are shown in Table 1.

[0102] Table 1 Ni prepared in Example 1-Example 5 and Comparative Example 1 x Co 1-x / MoP@NC nanocatalyst

[0103] Catalytic Hydrolysis of Ammonia Borane to Produce Hydrogen Performance List

[0104]

[0105] The results in Table 1 show that the Ni x Co 1-x All nanocatalysts in the / MoP@NC catalysts showed 100% H2 selectivity in the hydrolysis of ammonia borane to produce hydrogen. The catalytic reaction rate of the catalyst first increased and then decreased with the increase of the molar ratio of Ni to Co. When the molar ratio of Ni to Co was 8:2, the nanocatalyst showed the best performance in the hydrolysis of ammonia borane to produce hydrogen. This shows that there is a strong synergistic effect between Ni and Co. The electronic structures of the catalysts prepared with different molar ratios of Ni and Co are also different, which makes the final Ni x Co 1-x / MoP@NC nanocatalysts have different catalytic performances in the reactions.

[0106] Although the Co / MoP@NC nanocatalyst prepared in Comparative Example 1 showed 100% H2 selectivity in the hydrolysis of ammonia borane, the catalytic reaction rate was slow. x Co 1-x / MoP@NC nanocatalyst has better catalytic effect.

[0107] Embodiment 14

[0108] The Ni prepared by Examples 1, 6 and 8 of the present invention 0.8 Co 0.2 The / MoP@NC nanocatalyst catalyzes the hydrolysis of ammonia borane to produce hydrogen. The catalyst was placed in a 50 mL round-bottom flask containing 5 mL of deionized water, and 31.8 mg (1.0 mmol) of ammonia borane was added at 298 K and atmospheric pressure for reaction. The hydrogen production performance is shown in the figure Fig. 9 The conditions for catalyst preparation and the results of the catalytic reaction are shown in Table 2.

[0109] Table 2 Ni prepared in Example 1 and Example 6-Example 8 0.8 Co 0.2 / MoP@NC nanocatalyst

[0110] Catalytic Hydrolysis of Ammonia Borane to Produce Hydrogen Performance List

[0111]

[0112] The results in Table 2 show that Ni 0.8 Co 0.2 The selectivity and activity of / MoP@NC nanocatalyst for the production of hydrogen from the hydrolysis of ammonia borane increased first and then decreased with the increase of the amount of MoP@NC. When the amount of carrier was very small, the activity of the catalyst was relatively low. This was mainly because the amount of carrier was too small, resulting in an excessively high active metal loading, and the metal nanoparticles could not be dispersed, so the catalytic performance was poor. However, when the amount of carrier was increased to 20 mg, the catalyst had the best catalytic activity. Finally, when the amount of carrier was further increased, the activity of the catalyst decreased slightly. This shows that the catalyst can effectively disperse the metal nanoparticles and improve the catalytic activity, but when the amount of carrier was too much, it would make it difficult for the active metal to contact with ammonia borane, and thus the performance would decrease.

[0113] Embodiment 15

[0114] The Ni prepared in Example 1 of the present invention 0.8 Co 0.2The / MoP@NC nanocatalyst catalyzes the hydrolysis of ammonia borane to produce hydrogen at different temperatures. The catalyst was placed in a 50 mL round-bottom flask containing 5 mL of deionized water, and 31.8 mg (1.0 mmol) of ammonia borane was added at 288 K, 293 K, 298 K, and 303 K under normal pressure to react. The hydrogen production performance is shown in the figure below. Fig.10 The conditions for catalyst preparation and the results of the catalytic reaction are shown in Table 3.

[0115] Table 3 Ni prepared in Example 1 0.8 Co 0.2 / MoP@NC nanocatalyst

[0116] Table of performance of hydrogen production by catalytic hydrolysis of ammonia borane at different catalytic temperatures

[0117]

[0118] The results in Table 3 show that Ni 0.8 Co 0.2 / MoP@NC nanocatalysts catalyzed the hydrolysis of ammonia borane to produce hydrogen and showed 100% H2 selectivity. The catalytic reaction rate and reaction activity were significantly improved with the increase of temperature. This is mainly attributed to the fact that high temperature can activate the catalyst and thus effectively improve the catalytic reaction activity.

[0119] It can also be seen that at 298 K, the prepared Ni 0.8 Co 0.2 The hydrolysis and dehydrogenation of ammonia borane catalyzed by / MoP@NC nanocatalyst only takes 0.33 min, and its turnover frequency (TOF) value is as high as 257 min -1 .

[0120] Example 16

[0121] The Ni prepared in Example 1 of the present invention 0.8 Co 0.2 The / MoP@NC nanocatalyst catalyzes the hydrolysis of ammonia borane to produce hydrogen. The catalyst was placed in a 50 mL round-bottom flask containing 5 mL of deionized water. 31.8 mg (1.0 mmol) of ammonia borane was added at 298 K and reacted for 5 cycles. The hydrogen production performance is shown in the figure. Fig.11 shown.

[0122] from Fig.11 It can be seen that Ni 0.8 Co 0.2 / MoP@NC nanocatalyst has good cyclic stability for hydrogen production by hydrolysis of ammonia borane. After repeated use for 5 times, the catalyst activity and gas production did not decrease significantly, indicating that the catalyst has good catalytic activity and cyclic stability.

[0123] The Ni prepared by the present invention x Co 1-x The excellent activity of the / MoP@NC nanocatalyst is attributed to the fact that the modification of MoP NPs enhances the hydrophilicity of the catalyst, allowing the support to effectively adsorb metal precursor salt ions, which is conducive to the formation of Ni x Co 1-x / MoP nanoheterogeneous structure to obtain a high-performance catalyst. In addition, the modification of MoP NPs can also effectively adsorb and activate water molecules, accelerate the cleavage of OH bonds in water, and further form a dual-active site Ni x Co 1-x / MoP@NC catalyst.

[0124] In summary, the method for preparing the catalyst of the present invention is easy to operate and pollution-free. The obtained catalyst has the characteristics of small particle size, multiple catalytic active sites, etc., and has high catalytic activity and stability, and is a catalyst with great development prospects.

[0125] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0126] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A Ni x Co 1-x The application of / MoP@NC nanocatalyst in catalyzing the hydrolysis of ammonia borane to produce hydrogen is characterized in that: The temperature at which the nanocatalyst catalyzes the hydrolysis of ammonia borane to produce hydrogen is 288-303 K; The raw materials for preparing the nano catalyst include Ni x Co 1-x Nanoparticles, MoP nanoparticles and nitrogen-doped hollow carbon spheres, the Ni x Co 1-x The nanoparticles and the MoP nanoparticles form a nano heterostructure, wherein x=0.8; the content of Ni in the nanocatalyst is 9-10.5 wt%, and the content of Co is 2-3 wt%; the average particle size of the nanocatalyst is 4.7-6.9 nm; The Ni x Co 1-x The molar ratio of Ni to Co in the nanoparticles is 8:2, and the content of MoP in the nanocatalyst is 7.7-10.9 wt %; The thickness of the nitrogen-doped hollow carbon sphere is 30-50 nm, and the nitrogen content in the nitrogen-doped hollow carbon sphere is 2.6-3.4 wt %; The method for preparing the nanocatalyst comprises the following steps: MoP@NC powder was dispersed in deionized water, and nickel source precursor and cobalt source precursor were added. Ultrasonication was performed to obtain a uniform mixed solution, and finally a reducing agent was added to obtain Ni x Co 1-x / MoP@NC nanocatalyst; The preparation method of MoP@NC comprises the following steps: adding tetrakis hydroxymethylphosphonium chloride into deionized water, and dropping aniline under stirring; then adding ammonium molybdate tetrahydrate and stirring, washing the product after stirring, and drying to obtain a precursor powder; and finally calcining in a protective atmosphere to obtain MoP@NC black powder.

2. The use according to claim 1, characterized in that: The nickel source precursor is at least one of nickel chloride, nickel nitrate or nickel sulfate; the cobalt source precursor is at least one of cobalt chloride, cobalt nitrate or cobalt sulfate; and the reducing agent is sodium borohydride.

3. The use according to claim 1, characterized in that: The preparation method of MoP@NC comprises the following specific steps: 450-550 μL of tetrakis(hydroxymethyl)phosphonium chloride was added to 20-40 mL of deionized water, and 200-300 μL of aniline was slowly added dropwise under vigorous stirring to achieve successful polymerization; then 0.3-0.4 g of ammonium molybdate tetrahydrate was added and stirred for 8-16 hours. After stirring, the product was washed with deionized water and anhydrous ethanol, and dried in an oven at 70-90°C to obtain a precursor powder, and finally heated in a protective atmosphere at 0.5-1.5°C·min -1 The heating rate was increased to 800~900℃ and maintained for 0.5~1.5 h to obtain MoP@NC black powder.

Citation Information

Patent Citations

  • Preparation method of modified graphene oxide supported nickel-cobalt bimetallic nano-catalyst

    CN111111779A

  • Ni / P-Mo-coated Mo2C composite nano-catalyst for hydrogen production through hydrolysis of ammonia borane as well as preparation method and application of Ni / P-Mo-coated Mo2C composite nano-catalyst

    CN114904546A